Genotype environment interaction studies with cassava - Otoo, J.; Dixon, A.; Asiedu, Robert; Okeke, J.E.; Maroya, N.; Tougnon, K.; Okoli, O.; Tetteh, J.P.; Hahn, S.K. (International Society for Horticultural Science, 1994)
Multilocational trials were conducted in several agroecological zones in West Africa to assess the magnitude of genotype x environment (G x E) interaction and to identify stable varieties which could be used in breeding programs in the region. The reaction of the varieties to major cassava diseases and pests was also assessed. Ten clones, including 7 IITA improved cassava clones, were used in the study. Results from 22 trials conducted in a randomized complete block design revealed a highly significant G x E interaction for fresh root yield, African cassava mosaic virus, cassava bacterial blight, cassava green mite, and cassava mosiac. TMS 30572, TMS 63397, TMS 91934, and TMS 50395 were the most adaptable cultivars. TMS 30572 was the most stable of them. Some countries had cultivars adaptable to specific local environments.